CCR5 Disruption in Induced Pluripotent Stem Cells Using CRISPR/Cas9 Provides Selective Resistance of Immune Cells to CCR5-tropic HIV-1 Virus - HyunJun Kang; Petra Minder; Mi Ae Park; Walatta-Tseyon Mesquitta; Bruce E Torbett; Igor I Slukvin (Elsevier, 2015)
The chemokine (C-C motif) receptor 5 (CCR5) serves as an HIV-1 co-receptor and is essential for cell infection with CCR5-tropic viruses. Loss of functional receptor protects against HIV infection. Here, we report the successful targeting of CCR5 in GFP-marked human induced pluripotent stem cells (iPSCs) using CRISPR/Cas9 with single and dual guide RNAs (gRNAs). Following CRISPER/Cas9-mediated gene editing using a single gRNA, 12.5% of cell colonies demonstrated CCR5 editing, of which 22.2% showed biallelic editing as determined by a Surveyor nuclease assay and direct sequencing. The use of dual gRNAs significantly increased the efficacy of CCR5 editing to 27% with a biallelic gene alteration frequency of 41%. To ensure the homogeneity of gene editing within cells, we used single cell sorting to establish clonal iPSC lines. Single cell-derived iPSC lines with homozygous CCR5 mutations displayed the typical characteristics of pluripotent stem cells and differentiated efficiently into hematopoietic cells, including macrophages. Although macrophages from both wild-type and CCR5-edited iPSCs supported CXCR4-tropic virus replication, macrophages from CCR5-edited iPSCs were uniquely resistant to CCR5-tropic virus challenge. This study demonstrates the feasibility of applying iPSC technology for the study of the role of CCR5 in HIV infection in vitro, and generation of HIV-resistant cells for potential therapeutic applications.